TTIP – Potential Effects on Norway - Gabriel Felbermayr; Rahel Aichele; Inga Heiland; Arne Melchior; Marina Steininger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
The currently negotiated Transatlantic Trade and Investment Partnership between the EU and the United States of America will most likely affect countries, such as Norway which have close ties to the European production networks. Based on a CGE model, developed at the ifo institute, we structurally estimate the potential effects of TTIP for Norway's economy on sectoral level. The model captures the reality of global value chains and provides a multi-country multi-sector approach with rich intra- and international input-output linkages. The analysis shows that trade diversion and trade creation effects offset each other in Norway. A comprehensive agreement between the EU and the US would lead to an increase in Norwegian GDP per capita by 0.05%. However, the gain is entirely driven by positive value added changes in the energy sector. Without these gains, the aggregate effects would turn into a loss of -0.11% of current GDP.
Keywords: 330